Anti-S2 antibodies responsible for the SARS-CoV-2 infection-induced serological cross-reactivity against MERS-CoV and MERS-related coronaviruses - Sun, Siyuan; He, Jiaying; Liu, Luotian; Zhu, Yuzhen; Zhang, Qingsong; Qiu, Yinong; Han, Yuru; Xue, Song; Peng, Xiaofang; Long, Yiming; Lu, Tianyu; Wu, Wei; et al. (Frontiers in Immunology, 2025)
Sarbecoviruses, such as SARS-CoV-2, utilize angiotensin-converting enzyme 2 (ACE2) as the entry receptor; while merbecoviruses, such as MERS-CoV, use dipeptidyl peptidase 4 (DPP4) for viral entry. Recently, several MERS-related coronaviruses, NeoCoV and PDF-2180, were reported to use ACE2, the same receptor as SARS-CoV-2, to enter cells, raising the possibility of potential recombination between SARS-CoV-2 and MERS-related coronaviruses within the co-infected ACE2-expressing cells. However, facing this potential recombination risk, the serum and antibody cross-reactivity against MERS/MERS-related coronaviruses after SARS-CoV-2 vaccination and/or infection is still elusive. Here, in this study, we showed that the serological cross-reactivity against MERS/MERS-related S proteins could be induced by SARS-CoV-2 infection but not by inactivated SARS-CoV-2 vaccination. Further investigation revealed that this serum cross-reactivity is due to monoclonals recognizing relatively conserved S2 epitopes, such as fusion peptide and stem helix, but not by antibodies against the receptor-binding domain (RBD), N-terminal domain (NTD) or subdomain-1 (SD1). Some of these anti-S2 cross-reactive mAbs showed cross-neutralizing activity, while none of them exhibited antibody-dependent enhancement (ADE) effect of viral entry in vitro. Together, these results dissected the SARS-CoV-2 infection-induced serological cross-reactivity against MERS/MERS-related coronaviruses, and highlighted the significance of conserved S2 region for the design and development of pan-β-coronaviruses vaccines.